Impact of flood inundation and water management on water and salt balance of the polders and islands in the Ganges delta. (1st September 2021) - Mainuddin, Mohammed; Kirby, John M.
Abstract: Inundation by sea water in coastal areas can devastate cropping; recovery from the impacts can be slow. We used a water and salt balance model of polders to investigate the impacts of and recovery from flood inundation by sea water. We applied the model to three polders in the Ganges delta: Amtali, with high rainfall and low salinity; Dacope with intermediate rainfall and salinity; and Gosaba, with lower rainfall and higher salinity. Dacope and Gosaba were inundated a few years prior to our study, and the model calibration is pertinent to the recovery period. The calculated evapotranspiration from the polder (indicating crop growth) was dramatically reduced following inundation, and the calculated salt concentration in the soil water and shallow groundwater greatly increased. The model simulations showed that recovery depends on several factors, in particular how well the soil in the polder is drained and therefore how well salt is flushed out. Our simulations suggest that with sound maintenance of infrastructure and sound management, particularly of soil drainage, the polders and islands of the Ganges delta could recover fairly quickly from inundation events. Highlights: A novel water and salt balance model was used to study impact of flood inundation in the Ganges delta. Recovery depends on how well the soil in the polder is drained and therefore how well salt is flushed out. Sound maintenance of infrastructure and sound management of soil drainage are necessary. The polders and islands of the Ganges delta could recover fairly quickly from inundation events.